THE EPISTEMOLOGICAL STRUCTURE OF TAFSIR IQTISADI (THE STUDY OF AT-TAFSIR AL-IQTISADI LI AL-QURâ€™AN AL-KARIM BY RAFIQ YUNUS AL-MASRI - Baharuddin, Didin; Anwar, Hamdani; Amalia, Euis (Al-Bayan: Jurnal Studi Ilmu Al- Qur’an dan Tafsir, 2021)
This article discusses the epistemological structure of At-TafsÄ«r al-Iqtiá¹£ÄdÄ« li al-Qur'Än al-KarÄ«m by RafÄ«q YÅ«nus al-Maá¹£rÄ«. The author of this tafseer is an economist, a researcher at the Center for Islamic Economic Studies University of Malik 'Abdul' AzÄ«z, and is active in Al-Jam'iyah Ad-Dauliyah li Al-IqtisÄd London. The author's background makes this book very interesting to study because not many economists have written tafsir studies. This article is a literature study employing a descriptive-analysis method and a historical-philosophical approach. This study shows that the interpretation of At-TafsÄ«r al-Iqtiá¹£ÄdÄ« li al-Qur'Än al-KarÄ«m was written in a tartib mushafi model, and predominantly used tafsÄ«r bi ar-ra'yi with the nuances of the tafsÄ«r iqtiá¹£ÄdÄ«. The nuances of the iqtiá¹£ÄdÄ« interpretation come from tafsÄ«r Ê»ilmÄ«, which shows scientific theories from the Qurâ€™an. Through the tafsÄ«r iqtiá¹£ÄdÄ«, RafÄ«q YÅ«nus al-Maá¹£rÄ« attempted to show that the Qurâ€™an can be interpreted using an economic approach and argued that the Qurâ€™an provides the existence of economic theories. Among these theories are Musykilah an-Nadirah an-Nisbiyah (relative scarcity), at-Tafá¸Ä«l az-ZamanÄ« (time preference), and Taâ€™dzÄ«m al-manÄfiâ€™ (profit maximisation).